Employee working with ethyl cellulose at Hercules Hopewell plant - Hercules Incorporated (1940)
Close-up view of an unidentified employee removing a sample of ethyl cellulose from a machine at the Hercules Powder Company plant in Hopewell, Virginia. Per notations accompanying the photograph, the sampling was one of several control steps applied during the manufacture of ethyl cellulose. Ethyl cellulose manufactured by the Hercules Powder Company was commonly purchased by a variety of public and private industries as a raw material for use in plastics, films, lacquers, and other materials. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Employees; Chemical industry; Ethylcellulose; Hercules Incorporated; Corporations; Cellulose; Machinery